BRAIN GAIN OR BRAIN DRAIN? RETHINKING EDUCATIONAL MIGRATION FROM PUNJAB, INDIA (Lex localis - Journal of Local Self-Government, 2025)
Educational migration is a defining global phenomenon of the 21st century, representing a significant movement of human capital across international borders. Beyond individual ambition, these flows serve as a critical indicator of national economic health, social aspirations, and the perceived quality of education systems. According to the World Migration Report, the scale of this movement is immense, with the total number of international migrants reaching 272 million in 2019, accounting for 3.5 percent of the world's population. For students, the pursuit of internationally recognized qualifications, coupled with the promise of better career opportunities, has transformed higher education into a global market place. This paper examine the increasing trend of educational migration from Punjab. The authors introduce migration as a global phenomenon, noting that India is a major sending nation for international students, with educational migration being a significant form of movement driven by aspirations for better, quality education and internationally recognized qualifications. Further focuses on Punjab, a state with a long history of international migration, highlighting that both socio-economic factors like agrarian crisis and poor quality of higher education within the state are pushing youth to seek opportunities abroad, leading to a significant "brain drain." Punjab has a long and storied history of international migration, driven for decades by economic and social factors. However, the recent surge in migration for educational purposes represents a new and alarming chapter. This is no longer a gradual trend but a mass exodus of the state's youth, fueled by a complex interplay of hope for a better future abroad and disillusionment with the opportunities at home. The scale of this movement, when quantified, reveals a critical contemporary crisis for the state. Finally, the source asserts that injudicious state policies favoring the rapid, private expansion of higher education, which has created issues with access, equity, and affordability, are a major cause of this crisis and subsequent youth emigration. The analysis concludes that this trend is a direct outcome of injudicious neo-liberal state policies that have failed to retain and nurture local talent, leading to a state of "despondency, despair and decay" and posing severe long-term social, political, and economic risks for Punjab.